2019
DOI: 10.3389/fimmu.2018.03101
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Composition in Human Non-small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) is the leading cause of cancer-related death in the world. Immunological analysis of the tumor microenvironment (immunoscore) shows great promise for improved prognosis and prediction of response to immunotherapy. However, the exact immune cell composition in NSCLC remains unclear. Here, we used flow cytometry to characterize the immune infiltrate in NSCLC tumors, non-cancerous lung tissue, regional lymph node, and blood. The cellular identity of >95% of all CD45+ immune cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
201
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 252 publications
(233 citation statements)
references
References 67 publications
14
201
1
Order By: Relevance
“…Besides, the KEGG pathway enrichment displayed that the DEGs mostly clustered in the Cytokine−cytokine receptor interaction, the Chemokine signaling pathway, and the Viral protein interaction with cytokine and cytokine receptor. Consistent with these results, previous studies have shown that the biological processes of the immune system are critical to the formation of a complicated LUAD tumor microenvironment 10,30,[37][38][39] . In the past few years, the understanding of the immunological characteristics of LUAD has increased, and the development of effective LUAD immunotherapy strategies has drawn wide attention [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Besides, the KEGG pathway enrichment displayed that the DEGs mostly clustered in the Cytokine−cytokine receptor interaction, the Chemokine signaling pathway, and the Viral protein interaction with cytokine and cytokine receptor. Consistent with these results, previous studies have shown that the biological processes of the immune system are critical to the formation of a complicated LUAD tumor microenvironment 10,30,[37][38][39] . In the past few years, the understanding of the immunological characteristics of LUAD has increased, and the development of effective LUAD immunotherapy strategies has drawn wide attention [40][41][42][43][44] .…”
Section: Discussionsupporting
confidence: 86%
“…For example, levels of immune cell infiltration have been reported to be related to prognosis, and the activity of both immune and stromal cells has been shown to predict overall cancer survival 8 . Each component of the microenvironment plays an important role in LUAD, and therefore has a significant impact on clinical outcomes 5,[9][10][11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is no consensus in the literature on whether the high density of macrophages is detrimental or beneficial in lung cancer, while few recent reports demonstrated the correlation between prognosis and patient survival with the density of particular phenotype of macrophages. The prolonged patient survival correlated with a high density of M1 macrophages, while poor prognosis correlated with a high density of M2 macrophages in tumor islets (14)(15)(16)(17)(18)(19). Evidences suggest that cytokines secreted by TAMs induce hyperproliferative, anti-apoptotic, and metastatic responses in lung cancer, offering a potential immunotherapeutic option for its treatment (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Despite advances in diagnosis and therapy, the 5‐year survival rate of patients with NSCLC has been fairly poor over the past several years. It is imperative for us to well understand the molecular mechanism of NSCLC development and progression for providing new strategies in the early diagnosis and treatment of NSCLC 1,2 …”
Section: Introductionmentioning
confidence: 99%
“…It is imperative for us to well understand the molecular mechanism of NSCLC development and progression for providing new strategies in the early diagnosis and treatment of NSCLC. 1,2 XB130, also known as actin filament associated protein 1-like 2, is a novel multifunctional adapter protein. [3][4][5] First, XB130 crosslinks actin filaments (F-actin), promoting cell endocytosis, migration, and invasion.…”
Section: Introductionmentioning
confidence: 99%